2017
DOI: 10.1021/acssuschemeng.7b02282
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antioxidant Performance of Lignin and Quercetin Mixtures

Abstract: A natural, effective, and inexpensive hindered phenolic antioxidant mixture was prepared by blending lignin into quercetin. The antioxidant performance of lignin and quercetin mixture was analyzed by determining the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity and a low-cost and high-efficiency ratio was found to be 4:1 (w/w). After UV radiation for 4 h, the DPPH scavenging ratio of the quercetin/lignin mixture decreased only 13.8%, while that of quercetin and lignin decreased 42.9% and 28.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…DPPH (2,2-diphenyl-1-picrylhydrozyl) (Sigma Aldrich; Dorset, UK) radical was employed to measure the antioxidant activity of the produced tablets based on the radical scavenging property of the LIG [26,49]. For this purpose, LIG, MCC, and their blends, according to the different tablet compositions, were dissolved in a dioxane (Sigma Aldrich; Dorset, UK)/water (90:10, vol/vol) solution with a concentration of 400 mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPPH (2,2-diphenyl-1-picrylhydrozyl) (Sigma Aldrich; Dorset, UK) radical was employed to measure the antioxidant activity of the produced tablets based on the radical scavenging property of the LIG [26,49]. For this purpose, LIG, MCC, and their blends, according to the different tablet compositions, were dissolved in a dioxane (Sigma Aldrich; Dorset, UK)/water (90:10, vol/vol) solution with a concentration of 400 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…This compound provides mechanical protection to the plant. Moreover, LIG protects the plants from external biological and chemical stresses as it possesses antioxidant and antimicrobial properties [24,25,26,27,28]. LIG is one of the most abundant polymers on Earth, second after cellulose [11,22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…15 It has also been shown that adding lignin to quercetin can produce a green alternative to the synthetized antioxidants that are in use in food, cosmetics, and pharmaceuticals. 16 In a recent study, a stable nanodrug carrier was formed by the self-assembly of alkali lignin (AL) with the bioactive molecule resveratrol (RSV) and Fe 3 O 4 magnetic nanoparticles, which strongly supported the AL nanoparticle's application as a highly efficient nanodelivery. 17 Different studies examined the potential of lignin as a bio-based adsorbent.…”
Section: Introductionmentioning
confidence: 98%
“…LIG is a biopolymer present in the support tissues of vascular plants and provides chemical and mechanical protection from external stresses [17]. Moreover, it has been reported that LIG presents antioxidant and antimicrobial properties [18,19,20,21]. Among other alternatives, LIG-based materials have attracted the attention of researchers [17,22,23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%